2022
DOI: 10.1111/nmo.14473
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of small intestine pacing parameters for modulation of gut function

Abstract: Background and Purpose:The efficacy of conventional treatments for severe and chronic functional motility disorders remains limited. High-energy pacing is a promising alternative therapy for patients that fail conventional treatment. Pacing primarily regulates gut motility by modulating rhythmic bio-electrical events called slow waves.While the efficacy of this technique has been widely investigated on the stomach, its application in the small intestine is less developed. This systematic review was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
(224 reference statements)
0
5
0
Order By: Relevance
“…Significant research has been conducted on the small intestine to determine the effect of pacing on the GI TBME-00364-2023 motility [13]. However, investigators primarily mapped the rate of emptying [14], [35], [36], or used low-resolution manometry to determine the motility response [15], [19], [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant research has been conducted on the small intestine to determine the effect of pacing on the GI TBME-00364-2023 motility [13]. However, investigators primarily mapped the rate of emptying [14], [35], [36], or used low-resolution manometry to determine the motility response [15], [19], [37].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high-energy pacing targets the interstitial cells of Cajalthe pacemaker cells of the GI tractand therefore, can induce contractions if sufficient energy levels are applied [9], [10]. High-energy pacing has been shown to modulate GI function including: motility, absorbency, and bio-electrical activity [11]- [13]. The ability to modulate the contractile response of the small intestine via pacing is of importance to develop novel therapies for disorders such as post-operative ileus and chronic intestinal pseudo-obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Small intestine pacing has also been investigated for its clinical potential and has reported success in modulating the electrical and motility responses alongside absorption rates 18 20 . Electrical activity has been modulated to normalize dysrhythmias in intact and transected intestinal segments 20 – 22 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings are highly relevant in treating multi-factorial conditions such as prolonged post-operative ileus and short bowel syndrome, which can be challenging to treat with conventional approaches 26 , 27 . A recent systematic review revealed pacing orientation plays a key role in enhancing and inhibiting these responses, which highlights the critical role of individual pacing parameters and the need for their systematic evaluation 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation